The Culture of Correspondence in The Novel ( The Shadow of the Snake) by Youssif Zaidan (ALUSTATH JOURNAL FOR HUMAN AND SOCIAL SCIENCES, 2015)
This study talks about the novel (The Shadow of the Snake) which revolves around the women and their position in the cultures and literature, and the reality of the sacred status of women in the old religions and civilizations after being insulted and abused in the inherited customs and traditions. The novel tackles a two- part text. The first part deals with a stereo type of an Arab husband: arrogant and cruel .The second part is about the wife who is introduced to her mother through a collection of letters. Finding these letters is a major turning point in the novel; it is the climax by which the main character is introduced to the real status of women. The letters contain old songs and religious rhymes inspired by the folklore and through which we (the readers) are introduced to the etymology of different words and concepts. This novel presents a unique type of narration based on the technique of correspondence due to  its impact on the reader and its role in deducing the connotative meanings. The novel is open to endless readings and it puts women in their right places ; using a civilized  strategy and a right religious prospective.